The Utilization of Digital Technology in Public Health Services Utilization of Digital Technology in Public Health Services - Lea, Salshabilla April; Mutiara, Yusnidar Sari; Moely, Cut Mulyana; Marpaung, Mimbi Gusrera; Purba, Sri Hajijah (AMK : Abdi Masyarakat UIKA, 2024)
The use of digital technology has brought significant changes in the public health sector. This article analyzes policies related to the use of digital technology in public health services, focusing on innovations such as telemedicine, wearable devices, and electronic health information systems. The results of the study show that digital technology improves the efficiency, accessibility, and quality of health services, while supporting disease prevention and individual health management. However, challenges such as limited infrastructure, data privacy, as well as digital skills need to be addressed. Collaboration between the government, health institutions, and the community is the key to optimizing the application of digital technology in health services.